ICTs, citizens and governance : after the hype! - Meijer, Albert, 1967-; Boersma, Kees; Wagenaar, Pieter (Innovation and the public sector, 2009)
Hypes can be functional in triggering processes of change, but one should be able to distinguish a 'trigger' from a realistic set of expectations. This book aims to help researchers and practitioners to understand hypes about ICT and government without becoming cynical. It combines an analysis of the discourse with an analysis of practices.